Tunable interacting composite fermion phases in a half-filled bilayer-graphene Landau level - Zibrov, A. A.; Kometter, C.; Zhou, H.; Spanton, E. M.; Taniguchi, T.; Watanabe, K.; Zaletel, M. P.; Young, A. F. (Nature (London), 2017)
Various fractional quantum Hall phases are observed in a new generation of bilayer-graphene-based van der Waals heterostructures, including an even-denominator state predicted to harbour non-Abelian anyons. Graphene sandwich fills quantum phase gaps In the past decade, graphene has emerged as an important platform for discovering exotic phases that can arise in the fractional quantum Hall regime. In this regime, electrons confined to two dimensions are subjected to high magnetic fields and the strong interactions form composite quasiparticles. Andrea Young and colleagues have developed an exceptionally high-quality platform for such studies. They encapsulate bilayer graphene in hexagonal boron nitride and sandwich the structure between graphite electronic gates. As a result, they can clearly resolve various fractional quantum Hall phases, including a sought-after 'even-denominator' state, which refers to the fraction of filling of the so-called Landau states that arise in a magnetic field and that are associated with plateaus of quantized conductance. This phase is of particular interest as it is predicted to harbour non-Abelian anyons as emergent quasiparticles, which have topological properties that could be used for storing quantum information. Non-Abelian anyons are a type of quasiparticle with the potential to encode quantum information in topological qubits protected from decoherence 1 . Experimental systems that are predicted to harbour non-Abelian anyons include p-wave superfluids, superconducting systems with strong spin–orbit coupling, and paired states of interacting composite fermions that emerge at even denominators in the fractional quantum Hall (FQH) regime. Although even-denominator FQH states have been observed in several two-dimensional systems 2 , 3 , 4 , small energy gaps and limited tunability have stymied definitive experimental probes of their non-Abelian nature. Here we report the observation of robust even-denominator FQH phases at half-integer Landau-level filling in van der Waals heterostructures consisting of dual-gated, hexagonal-boron-nitride-encapsulated bilayer graphene. The measured energy gap is three times larger than observed previously 3 , 4 . We compare these FQH phases with numerical and theoretical models while simultaneously controlling the carrier density, layer polarization and magnetic field, and find evidence for the paired Pfaffian phase 5 that is predicted to host non-Abelian anyons. Electric-field-controlled level crossings between states with different Landau-level indices reveal a cascade of FQH phase transitions, including a continuous phase transition between the even-denominator FQH state and a compressible composite fermion liquid. Our results establish graphene as a pristine and tunable experimental platform for studying the interplay between topology and quantum criticality, and for detecting non-Abelian qubits.